Functional Characterization of Odorant Binding Protein PyasOBP2 From the Jujube Bud Weevil, Pachyrhinus yasumatsui (Coleoptera: Curculionidae) - Hong, Bo; Chang, Qing; Zhai, Yingyan; Ren, Bowen; Zhang, Feng (Frontiers in Physiology, 2022)
Odorant binding proteins (OBPs) play an important role in insect olfaction. The jujube bud weevil Pachyrhinus yasumatsui (Coleoptera: Curculionidae) is a major pest of Zizyphus jujuba in northern China. In the present study, based on the antennal transcriptome, an OBP gene of P. yasumatsui (PyasOBP2) was cloned by reverse transcription PCR (RT-PCR). Expression profile analyses by quantitative real-time PCR (qRT-PCR) revealed that PyasOBP2 was highly expressed in the antennae of both male and female P. yasumatsui adults, while its expression was negligible in other tissues. PyasOBP2 was prokaryotically expressed, and purified by Ni-NTA resin. The fluorescence competitive binding assays with 38 plant volatiles from Z. jujuba showed that PyasOBP2 could bind with a broad range of plant volatiles, and had strongest binding capacities to host-plant volatiles like ethyl butyrate (Ki=3.02 μM), 2-methyl-1-phenylpropene (Ki=4.61 μM) and dipentene (Ki=5.99 μM). The three dimensional structure of PyasOBP2 was predicted by homology modeling, and the crystal structure of AgamOBP1 (PDB ID: 2erb) was used as a template. The molecular docking results indicated that the amino acid residue Phe114 of PyasOBP2 could form hydrogen bonds or hydrophobic interactions with some specific ligands, so this residue might play a key role in perception of host plant volatiles. Our results provide a basis for further investigation of potential functions of PyasOBP2, and development of efficient monitoring and integrated pest management strategies of P. yasumatsui.